Morphological and molecular characters of freshwater shrimp of Macrobrachium pilimanus species group in Opak, Winongo and Sempor Rivers, Yogyakarta - Silmi, Malya Adzillina; Eprilurahman, Rury; Trijoko, Trijoko; Hakim, Lukman (Jurnal Biologi Udayana; Vol 25 No 1 (2021): JURNAL BIOLOGI UDAYANA, 2021)
Macrobrachium is a genus of the Crustacea subphylum with the highest diversity. Identification of the morphology of the genus Macrobrachium is mostly challenging due to the characters for species level identification are complicated, whereas many characters are common to all Macrobrachium species. In addition, it is difficult to identify morphology because of the influence of social dominance in males. Therefore, another approach is needed to identify Macrobrachium accurately, one of which is by barcoding DNA using the 16S mitochondrial gene. This study was aimed to determine the morphological and molecular characters of Macrobrachium pilimanus species group based on the 16S mitochondrial gene from the Opak, Winongo, and Sempor rivers, in Daerah Istimewa Yogyakarta. Furthermore, shrimp samples were identified based on morphological, meristic, and morphometric characters. Meanwhile, molecular analysis uses 16Sar as forward primer and 16Sbr as reverse primer. Based on the morphological identification results, the shrimp samples obtained could only be identified up to the level of the Macrobrachium genus. In addition, the shrimp samples can also be included in the Macrobrachium pilimanus species group based on the general characteristics of the species group. The shrimp samples in this study have highest similarities in character with the species M. pilimanus and M. empulipke distributed in Java. Based on molecular analysis, sample from Winongo River (WNM1) has a similarity of 87.63% with Macrobrachium forcipatum (JQ362454.1) and 87,02% with M. dienbienphuense (JQ390474.1), which means that it is a different species from the species in the GenBank. Macrobrachium forcipatum and M. dienbienphuense are members of M. pilimanus species group. The conclusion of this research is that all the samples are member of M. pilimanus species group.